Productivity Assessment in Roofing and Wall Painting Works Using Direct Observation Methods at Construction Site - Muhammad Hafizuddin Isa; Siti Khalijah Yaman (Journal of Structural Monitoring and Built Environment, 2026)
The productivity of the construction industry is influenced by factors such as labour management, worker welfare, and coordination. However, challenges like inadequate training and poor resource allocation can hinder productivity, especially in tasks like roofing and wall painting. This study investigates worker productivity at two sites, RTM Building and Gapam Mosque in Melaka, focusing on roofing (914.2 m² and 136 m²) and wall painting works (2560.7 m² and 1015 m²). Using direct observation over two months, the study recorded average productivity rates of 40.88 m²/h for roofing and 18.65 m²/h for wall painting. Roofing showed higher productivity due to simpler material application and less detailed work. Factors such as task delays, insufficient resources, and uneven labour distribution were identified as key productivity barriers. By addressing these challenges and optimizing skilled labour, the study highlights ways to improve productivity and enhance construction project outcomes.